On a combined theory of pay level satisfaction. (3rd November 2017) - Yao, Yong Heng (Angus); Locke, Edwin A.; Jamal, Muhammad
Summary: For decades, research on pay level satisfaction has focused on two theories and one approach: the direct link theory, the discrepancy theory, and the no‐difference‐scores approach. However, there are still unsolved puzzles facing pay level satisfaction research. We develop a combined theory to consider the impact of the interaction of reported pay and pay discrepancy. With this newly developed theory, we expect that (a) both reported pay and pay discrepancy have main effects on pay level satisfaction; (b) reported pay and pay discrepancy also interact with each other, in that the effect of pay discrepancy on pay level satisfaction decreases as pay level increases; (c) equitable payment is more related to pay level dissatisfaction when pay level is low; and (d) overpayment in general is related to pay level satisfaction, not dissatisfaction. An empirical study ( N = 481) using four types of comparison standards was conducted, and the results supported our predictions. The findings of our study have important implications for both academic research and management practice.